Pengaruh Gaya Kepemimpinan Transformasional, Kedisiplinan, dan Lingkungan Kerja terhadap Kinerja Karyawan PT. ARMY - Agus Kurniawan; Siti Annisa Wahdiniawati (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the influence of Transformational Leadership Style, Work Discipline, and Work Environment on Employee Performance at PT. ARMYs. The population in this study are employees who are still actively working at PT. ARMYs. The number of samples used was 84 respondents. Data collection was carried out using survey methods and questionnaires. By using random sampling technique. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) v.26.